Evaluasi Electronic Health Record (EHR) dengan Metode PIECES di Unit Rekam Medis Pusat RSUPN dr. Cipto Mangunkusumo - Ines Meiyola Pradanthi; Maya Weka Santi; Atma Deharja (Politeknik Negeri Jember, 2020)
National Center General Hospital Dr. Cipto Mangunkusumo is one of the hospitals whose services haveused Hospital Management Information System (SIMRS). The SIMRS used in RSCM is called the ElectronicHealth Record (EHR). In its application, there were still obstacles that made the staff less satisfied with theEHR, one of which was the loading of the EHR. The purpose of this study is to evaluate the EHR in termsof user satisfaction using the PIECES method (performance, information, economic, control, efficiency,service). This type of research is qualitative research, by describing the results of interviews andobservations that have been conducted by researchers and assessed by the PIECES method. Respondentsin this study were 1 filling officer, 1 reporting officer, 1 warehouse officer, and 1 expedition officer. The resultsobtained in this study are that the EHR performance has produced data according to user needs and thereis still a fairly long loading. EHR is able to provide quality information that is easily understood and has beenintegrated with BPJS. that the EHR can produce data according to user needs and the EHR still needs timeif the officer inputs or loads. The EHR has a use value because it is integrated with BPJS Health and alsohas an EHR officer or improvement team. EHR users feel that having an EHR makes it easy for EHR userswhen performing health services such as searching for patient files and making reports. The conclusion isthat the EHR makes it easy for users to do their work. Suggestions given by researchers are to the UMSI toupdate the EHR and perform maintenance on the system and hardware.